2020
DOI: 10.3390/cancers13010043
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Solid Tumors and Gut Microbiota: The Correlation—A Special Reference to Colorectal Cancer

Abstract: Over the last few years, immunotherapy has been considered as a key player in the treatment of solid tumors. Immune checkpoint inhibitors (ICIs) have become the breakthrough treatment, with prolonged responses and improved survival results. ICIs use the immune system to defeat cancer by breaking the axes that allow tumors to escape immune surveillance. Innate and adaptive immunity are involved in mechanisms against tumor growth. The gut microbiome and its role in such mechanisms is a relatively new study field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 111 publications
(182 reference statements)
0
22
0
Order By: Relevance
“…Over the last few years, immunotherapy has revolutionized the therapeutic approach to cancer. Immune checkpoint inhibitors (ICIs), including anti-PD-1 and anti-CTLA-4 have become the most promising treatment, with prolonged responses and improved survival in both solid tumors (for example: melanoma and renal cell carcinoma, non-small cell lung cancer, and mismatch-repair deficient colorectal cancer) and lymphomas [ 71 , 72 , 73 , 74 ]. However, immunotherapy only benefits a subset of patients.…”
Section: Gut Microbiota Biomarkers Predicting Prognosis And/or Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, immunotherapy has revolutionized the therapeutic approach to cancer. Immune checkpoint inhibitors (ICIs), including anti-PD-1 and anti-CTLA-4 have become the most promising treatment, with prolonged responses and improved survival in both solid tumors (for example: melanoma and renal cell carcinoma, non-small cell lung cancer, and mismatch-repair deficient colorectal cancer) and lymphomas [ 71 , 72 , 73 , 74 ]. However, immunotherapy only benefits a subset of patients.…”
Section: Gut Microbiota Biomarkers Predicting Prognosis And/or Treatment Responsementioning
confidence: 99%
“…Alexander et al have proposed in their review the ‘TIMER’ mechanistic framework (from Translocation, Immunomodulation, Metabolism, Enzymatic degradation, and Reduced diversity and ecological variation) to explain how gut bacteria influence chemotherapy effects on the host [ 80 ]. Numerous preclinical studies have demonstrated the involvement of the gut microbiome in the efficacy of a range of chemotherapies such as cyclophosphamide [ 81 ], oxaliplatin [ 74 , 82 ] or gemcitabine [ 83 ] in CRC and other cancer types. More recently, a metagenome association study in lung cancer patients showed that Streptococcus mutans and Enterococcus casseliflavus were linked to better chemotherapy outcomes [ 84 ].…”
Section: Gut Microbiota Biomarkers Predicting Prognosis And/or Treatment Responsementioning
confidence: 99%
“…This novel insight into the role of altered tumor suppressors in immune evasion could guide novel immunotherapies which target or restore altered tumor suppressor genes in combination with other IT [179,180]. Additionally, unraveling the interplay of gut microbiota and IT may reveal approaches to increase abundance of immunostimulatory microbes and decrease abundance of immunosuppressive species to enhance IT efficacy [169,170,181]. Ongoing investigation of immune escape mechanisms will continue to reveal next-generation IT targets.…”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…Ongoing investigation of immune escape mechanisms will continue to reveal next-generation IT targets. For example, investigation of the interplay of gut microbiota and IT may reveal approaches to increase abundance of immunostimulatory microbes and decrease abundance of immunosuppressive species to enhance IT efficacy [ 197 , 198 , 234 ].…”
Section: Sensitizing Crc To Itmentioning
confidence: 99%